Clinical Characteristics and Risk Factors of Dengue Shock Syndrome in Children. Issue 12 (December 2016) - Lovera, Dolores; Martinez de Cuellar, Celia; Araya, Soraya; Amarilla, Sara; Gonzalez, Nicolás; Aguiar, Carlos; Acuña, Julia; Arbo, Antonio
Abstract : Background: Dengue shock syndrome (DSS) represents one of the most severe manifestations of dengue virus infection. The objective of the present study was to analyze the clinical and laboratory characteristics, risk factors and outcome of DSS in children. Methods: Patients <15 years old admitted with DSS during the 2012 and 2013 outbreak of serotype 2 of dengue virus in Paraguay were included. Demographic, clinical and laboratory data of patients with/without DSS were analyzed. Results: Of 471 children hospitalized with dengue, 354 patients (75%) presented with shock at admission or developed later. The mean age of patients with DSS was 10.2 ± 4 years (no difference with patients without shock), without gender preference. Rash (50% vs. 56%), myalgias (45% vs. 40%), vomiting (66% vs. 68%) and bleeding manifestations (24% vs. 21.2%) were similar for 2 groups. Similarly, there was no difference in the frequency of DSS between primary versus secondary infection cases (76.2% vs. 71.6%, P = 0.3). Age group >5 years [odds ratio (OR) 1.6, 95% confidence interval (CI): 1–2.8, P < 0.05), presence of abdominal pain (OR 2.5, 95% CI: 1.3–4.9, P = 0.006), an activated partial thromboplastin time prolonged (OR 4; 95% CI: 1.6–10, P < 0.001) and low fibrinogen level (OR 2.5; 95% CI: 1–5.9, P = 0.02) were found significantly associated with DSS. About 12% of patients required intensive care unit admission, and 2 patients died (lethality 0.35%). Conclusions: This study validated most of the clinical variables present in the current WHO guidelines as markers of severe disease and add additional variables that can help to predict the risk of progression to shock.